Riflessioni sul recupero del percorso sulle mura della Fortezza da Basso di Firenze - Antonella Valentini (Restauro Archeologico, 2020)
The essay deals with a particular topic within the broader theme concerning the restoration of the Fortezza da Basso in Florence: the recovery of the walk on the walls of the fortified complex. It is a place so central but almost unknown because it is not accessible, in which forgetfulness has created a singular vegetable microcosm inside the city, that it will be given to tourists and Florentines for a renewed use. This walk on the top of the Fortress is an interesting field of design experimentation that combines archeology, landscape and architecture. The article reflects on the transformation and intervention options in multiple stratigraphic places, between preservation of persistent historical values and renewal of using forms.